The art of diplomacy : how American negotiators reached historic agreements that changed the world - Eizenstat, Stuart; Kissinger, Henry A.; Baker, James A. (Lanham : Rowman and Littlefield, 2024)
"Longtime diplomat and negotiator Stuart E. Eizenstat covers every major contemporary international agreement, from the treaty to end the Vietnam War to the Kyoto Protocols and the Iranian Nuclear Accord. This book will be an indispensable volume to understand American foreign policy and provide invaluable insights on the art of negotiation for anyone involved in government or business negotiations"--
Includes bibliographical references and index.
Keywords: Diplomacy; Diplomats -- United States; Diplomatic negotiations in international disputes; United States -- Foreign relations